Effect of tool-sidewall outlet hole design on machining performance in electrochemical mill-grinding of Inconel 718. (May 2019) - Niu, Shen; Qu, Ningsong; Yue, Xiaokang; Li, Hansong
Abstract: Electrochemical mill-grinding (ECMG) combines electrochemical milling and electrochemical grinding in a single processing procedure, and can be used for both rough and finish machining of difficult-to-machine alloys. In the rough machining stage, improved tool designs, obtained by varying the number of rows of the tool-sidewall outlet holes and their mode of arrangement, are both introduced for the ECMG of Inconel 718. Four tools with different numbers of rows of tool-sidewall outlet holes are designed. The test results show that a higher maximum feed rate can be obtained by using an abrasive tool with four rows of tool-sidewall outlet holes. Experimental results on machining a slot with this tool indicate that the material removal rate is increased at higher applied voltage, electrolyte pressure, and feed rate, while the average slot width and sidewall flatness become smaller at higher electrolyte pressure and feed rate at fixed applied voltage. However, a major defect of the vertical alignment of tool-sidewall outlet holes is found to be the formation of an uneven profile on the machined sidewall, which gives rise to a large machining allowance for subsequent finishing. Therefore, an abrasive tool with a spiral arrangement of tool-sidewall outlet holes is proposed. The average sidewall flatness and the sidewall surface roughness obtained with the original tool are 549.6 μm and 2.509 μm, but they are only 340.5 μm and 1.65 μm with the new tool. In addition, the new tool is also applied for finish machining on the slot sidewall produced by rough machining. After the finish machining stage, the average sidewall flatness and the sidewall surface roughness decrease from 340.5 μm to 69.5 μm and from 1.65 μm to 0.648 μm, respectively.